2019
DOI: 10.3991/ijet.v14i21.10643
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Content of a Client-Server Technology Training Course: Set up and Collaborative Implementation of Local and Cloud-Based Remote Servers

Abstract: The integration of software solutions in the content of the training courses as a result of the socio-economic demand has a positive effect on the improvement of training the students for future professional activities. However, the latest achievements of hardware and software are not included in the content of the high education in a timely manner. Therefore, in our research we set the task to improve the content of the training course on the client-server technology using modern software capabilities. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is known that in the modern world great changes and innovations are taking place in the field of computer technology, computing systems and computation methods. Especially multi-core computing systems, clusters, supercomputers, client-server technologies [1] began to be used in all areas of education and science, economics and industry. Problem solving and learning methods are also changing, and computing systems and computation methods are improving.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in the modern world great changes and innovations are taking place in the field of computer technology, computing systems and computation methods. Especially multi-core computing systems, clusters, supercomputers, client-server technologies [1] began to be used in all areas of education and science, economics and industry. Problem solving and learning methods are also changing, and computing systems and computation methods are improving.…”
Section: Introductionmentioning
confidence: 99%
“…Several teachers have also applied micro-video resources to blending teaching mode discussions, and they have carried out application studies in different courses, which demonstrated this mode is suitable for the subjects with strong operability and practicality. Liu Yajuan et al (2019) found in the article Experience of Blending Teaching Course Design for Environmental Chemistry Based on Micro course and Inverted Classroom that the structure and difficulty of the course, as well as the assessment of the course, would affect the learning results [3][4][5]. Through review and summary of the related research literature for nearly three years, it is found that the research of teaching application mode based on micro course has achieved certain results.…”
Section: Introductionmentioning
confidence: 99%